Body fat. In and out of the fitness center - Galea, Ioan; Andrei, Liviu Vasile; Gorea, Adrian; Dobrin, Florian (Arena-Journal of Physical Activities, 2016)
A relevant aspect of physical condition is represented by the adipose tissue; it is actually the goal of those who visit frequently the gym. The purpose of this current research is to pinpoint the importance and the role of the personal trainer regarding the efficiency of the services offered to clients in a gym. Methods. The research developed in two phases in two fitness centers; in the first phase the subjects (N=20), divided in two groups, the control group (C.GR, N=10, M(y) =28.8Â±4.8y, M(h)=1.66Â±0.04m, M(w)Â =64.2Â±10.28kg) and the experimental group (E.GR, N=10, M(y)=30.4Â±5.8y, M(h)= 1.68Â±0.08y, M(w)= 62.7Â±8.52kg) accomplished a number of 30 ses- sions. At C.GR they worked by the classical method and at E.GR theyÂ worked by the personal trainer method. Both groups were determined at the beginning of the research (I.T) and at the end of the research (F.T) the fat areas in three parts: belly(b), arm(a) and hip(h) as well as BMI. In the second phase, the subjects (N=10), divided in two groups, the control group (C.GR , N=5, M(y)=29.4Â±8.2y, M(h)=1.69Â±0.15m, M(w)=71Â±21.4kg) andÂ the experimental group (E.GR, N=5, M(y)=30.8Â±4.4y, M(h)=1.71Â±0.01m, M(w)=83Â±17.4kg) attended a number of 30 sessions by the personal trainer method in the gym. Before the experiment started, each subject from E.GRÂ was calculated the daily water intake (from liquids and from food). DuringÂ the first 15 sessions, the subjects belonging to this group voluntarily gave up to a quantity of approximately 500 ml water/ day (DWI), and during the next 15 sessions to a quantity of approximately 1000 ml water/ day. Re- sults. Between the limitations of our research we can say that, the subjects who work by the personal trainer method have greater fat loss in relation to the subjects who work by classical methods. These losses are broader if as- sociated with modifications of the daily diet, in the case of our research we talk about the daily intake of liquids.